EXPLORING SOCIO-TECHNICAL FUTURES OF WORK: A NARRATIVE-BASED FORESIGHT APPROACH: Report of the Millennium Project Session at the Futures of Technologies Conference 2025 - Di Berardo, Mara; Heinonen, Sirkka; Taylor, Amos; Viitamäki, Riku; Virmajoki, Veli (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2025)
This report presents the process and the findings of the Millennium Project Special Session held at the Finland Futures Research Centre (FFRC) Conference in Turku, Finland on 11th June, 2025. The MP Session was conducted within the FFRC research project T-winning Spaces 2035 that is ongoing at University of Turku, exploring futures of work, work spaces, and new paradigm of work. The Twinning Spaces 2035 is a research project funded by the Research Council of Finland, and the European Union NextGenerationEU. It is headed by Aalto University with University of Turku and University of Tampere as partners. The Session was organised in co-operation between University of Turku, Aalto University, Millennium project, and the Finnish Society for Futures Studies. The session was an interactive Futures Clinique including futures provocations. The aim of the session was to delve deeper into the four radical narratives developed within T-winning Spaces 2035 project and ideate how to make these narratives more preferred. Here the modified Futures wheel was utilised to structure the ideation process. The findings included technological innovations, more well-being centric solutions and social process, which would help the personas of the narratives to deal with the problems and challenges they face.